A Novel CCM2 Gene Mutation Associated with Familial Cerebral Cavernous Malformation - Huang, Wen-Qing; Lu, Cong-Xia; Zhang, Ya; Yi, Ke-Hui; Cai, Liang-Liang; Li, Ming-Li; Wang, Han; Lin, Qing; Tzeng, Chi-Meng (Frontiers in Aging Neuroscience, 2016)
Background: Cerebral cavernous malformations (CCMs) are common vascular malformations that predominantly arise in the central nervous system and are mainly characterized by enlarged vascular cavities without intervening brain parenchyma. Familial CCMs (FCCMs) is inherited in an autosomal dominant pattern with incomplete penetrance and variable symptoms. Methods: Mutations of three pathogenic genes, CCM1, CCM2 and CCM3, were investigated by direct DNA sequencing in a Chinese family with multiple CCM lesions. Results: Four heterozygous variants in the CCM2 gene, including one deletion (c.95delC), a missense mutation (c.358G>A, p.V120I), one silent mutation (c.915G>A, p.T305T), and a substitution (c. *1452 T>C), were identified in the subjects with multiple CCM lesions, but not in a healthy sibling. Among these variants, the c.95delC deletion is a novel mutation which is expected to cause a premature termination codon. It is predicted to produce a truncated CCM2 protein lacking the PTB and C-terminal domains, thus disrupting the molecular functions of CCM2. Conclusions: The novel truncating mutation in the CCM2 gene, c.95delC, may be responsible for multiple CCM lesions in a part of FCCM. In addition, it may represent a potential genetic biomarker for early diagnosis of FCCM.